A framework proposition to identify customer value through lean practices. Issue 4 (20th March 2020) - Peralta, Carla Beatriz da Luz; Echeveste, Márcia Elisa; Lermen, Fernando Henrique; Marcon, Arthur; Tortorella, Guilherme
Abstract : Purpose: Customer value is the key to successful innovation management. This task is considered complex and abstract. For this reason, several models have been proposed to that end, among them, Lean approaches. Lean's background has been applied to value identification, providing many benefits. This paper aims at analyzing the practices employed to identify customer value through Lean approaches. Design/methodology/approach: Through a systematic literature review, the main Lean practices for customer value identification were categorized based on five main streams: (1) customer development, (2) customer value, (3) lean product, (4) lean start-up, and (5) lean innovation. These practices were organized into a framework that addresses value identification based on ideation, value prospection, requirements, construction and measurement, and value delivery. Findings: In total, 33 practices were found to support capturing the value from the customer's perception. Additionally, a discussion is provided on the complementarity and differences between practices. Originality/value: A framework is proposed to integrate the five streams and the corresponding practices for value identification. The results provide mechanisms that can benefit practitioners to better understand the value demanded by customers during innovation management. In fact, practitioners can use the proposed framework to identify value to customers in a holistic way. Academically, the results gather research on customer value and innovation management to contribute with a novel artifact for customer value identification in operations management using Lean approaches. Finally, a future research agenda on value identification is proposed.